Testing for maximum oxygen consumption has produced a brainless model of human exercise performance - Noakes, T. D. (British Journal of Sports Medicine, 2008)
Perhaps the hallmark study in human exercise physiology was performed by Nobel Laureate Professor AV Hill on himself in Manchester, England in the early 1920s. Hill circled an 88 metre grass running track at three different speeds each for 4 minutes while he measured his average oxygen consumption every 30 seconds (Hill and Lupton;1 fig 2 of that paper). He concluded that his oxygen consumption reached a maximum at 16 km/hour "beyond which no bodily effort can drive it".2 (page 1661) This experiment established the single most popular test in the exercise sciences - the progressive exercise test for the measurement of the maximum oxygen consumption (VO2max). The experimental protocol in this test forces the subject progressively to increase the work rate until voluntary exhaustion.